Consumptive Work in Coworking: Using Consumption Strategically for Work - Gruen, Adèle; Bardhi, Fleura (Journal of Consumer Research, 2025)
Abstract Consumption has always been part of the workplace, yet it has traditionally been seen as nonwork—an activity that depletes rather than creates value. In the knowledge and digital economy, however, consumption and work are becoming increasingly intertwined, calling for a relational perspective on consumption’s productive role. We develop this perspective through a four-year ethnography of coworking spaces across Paris and London, supplemented by post-pandemic archival data. We introduce consumptive work as the instrumentalization of consumption activities in the workplace to generate productive value. Consumptive work emerges within a postindustrial societal context where workplace culture is shaped by consumer ideology, leading to (1) customer entitlement in the workplace, (2) consumer desire toward the workplace, and (3) consumer lifestyle aspirations toward work. Consumptive work is characterized by inconspicuousness, boundarilessness, and communal and market exchange. While it can be empowering, it also fosters neo-normative alienation, particularly through performative play and leisure, and the pursuit of productive wellness. Ultimately, consumptive work reinforces evolving consumer desires and aspirations about office work and workplaces. This study advances interdisciplinary research on consumption and consumption ideology in the workplace, workplace alienation, new ways of working, and consumer research connecting work, home, and leisure.